2022
DOI: 10.1108/jfbm-10-2021-0131
|View full text |Cite
|
Sign up to set email alerts
|

Promoting family business in handicrafts through local tradition and culture: an innovative approach

Abstract: PurposeThe purpose of the study is to investigate the potentiality and dimensions of promoting handicraft family business practices in handicraft as well as the extent to highlight the local tradition and culture.Design/methodology/approachThis study is an insight from the existing relevant literature on family-owned businesses in handicrafts from time immemorial. Furthermore, data were collected from the 300 respondents using a purposive sampling procedure in which the rate of response was 67%. The structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 74 publications
1
35
0
Order By: Relevance
“…Family businesses play a significant role in the economic well-being of many countries worldwide (Camilleri and Valeri, 2021), as not only major producers of goods and services but also major suppliers for other industries, thus driving the gross national product (Deb et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Family businesses play a significant role in the economic well-being of many countries worldwide (Camilleri and Valeri, 2021), as not only major producers of goods and services but also major suppliers for other industries, thus driving the gross national product (Deb et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Family businesses play a significant role in the economic well-being of many countries worldwide (Camilleri and Valeri, 2021), as not only major producers of goods and services but also major suppliers for other industries, thus driving the gross national product (Deb et al, 2022). Between 67 and 90% of world businesses are operated by families, collectively employing half of the world's workforce (Obermayer et al, 2021;Veloso et al, 2021;Elmo et al, 2020;Royer and Bradley, 2020;Kiwia et al, 2020;Wang, 2010) and is labour intensive (Piramanayagam and Seal, 2021a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Kebete (2021) suggested that a realistic guideline and polices are essential for the development of emerging tourism destinations in the post pandemic era. Apart from the theoretical contributions, the findings of this study will enhance the managerial skills of businessman, regulating authority of this industry through generate the knowledge of travel risk management, managing service delivery system, and hygience and safety management by promoting rural tourism through local culture, heritage, and tradition (Deb et al, 2022). To implement the golas of SDG-2030 during the post COVID-19 era digital marketing i.e.…”
Section: Conclusion and Recommendationmentioning
confidence: 96%
“…Secondly, this study is only based on empirical analysis (quantitative research), future research should be beneficial by interviewing family business owners to gain a deeper understanding of their motivation and challenges in participating in online business networks to enhance business performance in the real business setting. Also, it would be interesting for future research to consider the benefits of online business networks and digital social capital on business development for family businesses in specific sectors and geographical locations that significantly rely on digital connectivity and technological devices such as tourism and hospitality, rural businesses, local handicraft businesses and so on (see Kumar et al, 2021;Shekhar et al, 2021;Tiwasing, 2021;Deb et al, 2022). Next, future research should explore the interaction between members within the social media business networks to understand how they use these online networks to improve their business performance since this information is not available in the LSBS 2015.…”
Section: Limitations and Future Researchmentioning
confidence: 99%